2020
DOI: 10.1007/s13304-020-00887-3
|View full text |Cite
|
Sign up to set email alerts
|

Graft factors as determinants of postoperative delirium after liver transplantation

Abstract: Post-operative delirium (POD) is a frequent complication after surgery, occurring in 15–20% of patients. POD is associated with a higher complications rate and mortality. Literature on POD after liver transplantation (LT) is limited, with the few available studies reporting an incidence of 10–47%. The aim of this study was analyzing pattern, risk factors and clinical impact of POD after LT. Data on donor and recipient characteristics, postoperative course and POD of consecutive adult LT recipients from March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Data regarding POD in the kidney transplant (KT) population are scarce. Herein, we present the result of a systematic review (SR), showing an incidence of 5.48% among patients undergoing single organ KT and 7% in recipients of multiple organ transplant, in accordance with other reports for transplanted patients [2].…”
supporting
confidence: 86%
“…Data regarding POD in the kidney transplant (KT) population are scarce. Herein, we present the result of a systematic review (SR), showing an incidence of 5.48% among patients undergoing single organ KT and 7% in recipients of multiple organ transplant, in accordance with other reports for transplanted patients [2].…”
supporting
confidence: 86%
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
“…Delirium was measured by research personnel in 171 studies (54.3%), a combination of research personnel and physicians in 5 studies (1.6%), and a physician in 139 studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous publication, donor factors, such as graft macrovesicular steatosis, emerged as possibly associated with the likelihood of post-LT delirium ( 33 ). We inluded recipient age and body mass index, and steatosis of liver graft into the analysis and did not find their relationship with delirium.…”
Section: Discussionmentioning
confidence: 99%